STRUCTURE AND CHEMISTRY OF GRAIN BOUNDARIES IN DEFORMED, OLIVINE + BASALT AND PARTIALLY MOLTEN LHERZOLITE AGGREGATES: EVIDENCE OF MELT-FREE GRAIN BOUNDARIES - Hiraga T.; Anderson I.M.; Zimmerman M.E.; Mei S.; Kohlstedt D.L. (My University, 2002)
Olivine grain boundaries in deformed aggregates of olivine + basalt and partially molten lherzolite were analyzed with various electron microscopy techniques to test for the presence of thin (0.5-10 nm) intergranular melt films. High-resolution transmission electron microscopy (HREM) observations reveal that most of the boundaries do not contain a thin amorphous phase, although a small fraction of grains are separated by relatively thick (~1 µm) layers of melt. However, due to the anisotropy of the olivine-melt interfacial energy, melt often tapers from a triple junction into an adjoining grain boundary over a length of 1 to 2 µm, giving an effective dihedral angle of only ~2°. The chemistry of olivine-olivine grain boundaries was analyzed using energy dispersive X-ray (EDX) profiling by scanning transmission electron microscopy (STEM) with a probe size of <1.5 nm. Ca, Al and Ti segregate to grain boundaries forming enriched regions of <7 nm width. Although these elements are concentrated in the glass phases, the presence of glass films with the same chemical composition as the bulk glass phases cannot explain concentrations of other elements such as Si and Al at the boundaries. Combined with the HREM results, the STEM/EDX profiling demonstrates the existence of chemical segregation between solid grains but the absence of thin, grain boundary melt films. Additionally, if melt films exist along all of the grain boundaries, as reported for similar samples by other groups, the rock should be substantially weakened. Creep experiments on the partially molten rocks analyzed in this study reveal little weakening at small melt contents, consistent with our observations of melt-free grain boundaries.